2017
DOI: 10.1158/1055-9965.epi-16-0891
|View full text |Cite
|
Sign up to set email alerts
|

Serum C-peptide, Total and High Molecular Weight Adiponectin, and Pancreatic Cancer: Do Associations Differ by Smoking?

Abstract: Background Studies examining associations between circulating concentrations of C-peptide and total adiponectin, two biomarkers related to obesity and insulin secretion and sensitivity and pancreatic ductal adenocarcinoma (PDA) risk have shown inconsistent results and included limited numbers of smokers. Methods We examined associations of these biomarkers and high molecular weight (HMW) adiponectin with PDA, overall, and by smoking status. We conducted a pooled nested case-control analysis in 3 cohorts (Pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…A case-control study showed no association of adiponectin with PDAC risk overall; however, higher adiponectin levels were associated with a reduction in PDAC risk among never smokers [111]. An influence of smoking on the risk of adiponectin on PDAC risk has been reported [112]. However, a Mendelian randomization study did not find an association of adiponectin with PDAC risk [93].…”
Section: Adiponectinmentioning
confidence: 98%
“…A case-control study showed no association of adiponectin with PDAC risk overall; however, higher adiponectin levels were associated with a reduction in PDAC risk among never smokers [111]. An influence of smoking on the risk of adiponectin on PDAC risk has been reported [112]. However, a Mendelian randomization study did not find an association of adiponectin with PDAC risk [93].…”
Section: Adiponectinmentioning
confidence: 98%
“…Michaud and colleagues reported a positive association that was stronger among nonsmokers, and this was seen only in nonfasting blood samples ( 25 ). On the other hand, the study by Nogueira and colleagues found an inverse association between plasma C-peptide levels and PDAC risk in current smokers and no association in never or former-smokers ( 26 ). These results indicate that the association of C-peptide levels with PDAC risk is somewhat dependent on smoking status, but further investigation into its role in PDAC development is required.…”
Section: Resultsmentioning
confidence: 99%
“…5A ) and also showed a certain degree of heterogeneity. Interestingly, like C-peptide levels, two studies reported an inverse association between circulating levels of adiponectin and PDAC risk, which was specific to never smokers ( 26, 47 ). We also identified two studies that looked at the association between another adipokine, leptin and PDAC risk and one of them reported no clear overall association ( 48 ), whereas the second study by Babic and colleagues found higher levels of leptin, indicating an increased risk in men but not in women ( 49 ).…”
Section: Resultsmentioning
confidence: 99%
“…), thereby preventing vascular leakage [40]. Research by Nogueira et al Showed that C-peptide levels are inversely related to pancreatic duct adenocarcinoma in current smoking patients [41].…”
Section: The Role Of C-peptide In Neoplastic Diseasesmentioning
confidence: 99%